2014
DOI: 10.1016/j.redox.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q supplementation in pulmonary arterial hypertension

Abstract: Mitochondrial dysfunction is a fundamental abnormality in the vascular endothelium and smooth muscle of patients with pulmonary arterial hypertension (PAH). Because coenzyme Q (CoQ) is essential for mitochondrial function and efficient oxygen utilization as the electron carrier in the inner mitochondrial membrane, we hypothesized that CoQ would improve mitochondrial function and benefit PAH patients. To test this, oxidized and reduced levels of CoQ, cardiac function by echocardiogram, mitochondrial functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Although the role of CoQ10 has extensively been explored in healthy subjects and in different pathological conditions, its effects on EF have mainly been described in patients with CVD and related chronic states such as type 2 diabetes and CAD [46,47]. In a study involving CoQ10 supplementation in healthy non-smokers with hypercholesterolemia, Raitakari et al found baseline FMD values that were comparable to those observed in our population, lending support to the notion that hypercholesterolemia alone is sufficient to induce ED in the absence of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of CoQ10 has extensively been explored in healthy subjects and in different pathological conditions, its effects on EF have mainly been described in patients with CVD and related chronic states such as type 2 diabetes and CAD [46,47]. In a study involving CoQ10 supplementation in healthy non-smokers with hypercholesterolemia, Raitakari et al found baseline FMD values that were comparable to those observed in our population, lending support to the notion that hypercholesterolemia alone is sufficient to induce ED in the absence of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the interim, CoQ 10 alone or with combination of TAU plunged ascites mortality to levels even lower that the control. There is a great deal of evidence on the role of CoQ 10 in cardiometabolic disorders (Zozina, Covantev, Goroshko, Krasnykh, & Kukes, 2018) and pulmonary arterial hypertension (Sharp et al, 2014;Yousefi, Khajali, Hassanpour, & Khajali, 2013) through improved mitochondria function and enhanced NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Isik T et al 20 have shown RDW levels as an independent correlate predictor index of adverse outcomes also associated with both presence and severity of isolated ischemia than baseline RDW levels measured at ischemic patients and controls. Sharp J et al 21 considered mitochondrial dysfunction as a fundamental abnormality in the vascular endothelium and smooth muscle of patients with pulmonary arterial hypertension (PAH). Coenzyme Q (CoQ) is essential for mitochondrial function and effi cient oxygen utilization as the electron carrier in the inner mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%